O professor de educação especial frente às políticas públicas de educação inclusiva: um estudo sobre identidade - Lino, Débora Maria de Paula (2006)
This work is aimed at understanding the constitution process of identity of a teacher specialized in special education, who works for the State Public Education, in face of the present inclusive educational policy. In the first part, we traced some elements of the theory of identity from the point of view of Antonio da Costa Ciampa, under the aspects of its social-historical psychology. In the second part of the work we went through some questions about education focusing on the special education history; the legislation about special and inclusive education, with special attention to the Federal and State resolutions; to the special public education policies in the state of São Paulo and to the formation of the specialist teacher in special education. The data collected from non directive interviews based on the teacher s life history narrative shows that the interviewed teacher went through several changes throughout her development as an educator, however there is still a long way to go in order to assume new roles that will enable her to contribute to the effectiveness of the inclusive school. It is important to move from an agreeable speech towards inclusion to an effective action of commitment with this process